Implementation research to develop an optimized delivery model for effective implementation of evidence-based interventions to reduce stillbirth in India: A study protocol - Gadapani Barsha Pathak; Reema Mukherjee; Vani Kandpal; Abhishek Agarwal; Prem Mony; Maryann Washington; Sarmila Mazumder; N. K. Arora (PLoS ONE, 2025)
Background Stillbirth remains a public health concern in India, despite a decrease in reported rates. Inconsistent data collection hampers clear understanding the burden of stillbirth, and interventions for its reduction are scattered across various national programs. This research aims to explore effective strategies to improve the delivery and uptake of high-quality antenatal and intrapartum care services which have the potential to reduce stillbirth rates in various states of India. Methods This mixed-method, multi-site study in India will be conducted in three phases: Phase 1: Formative Phase; Phase 2: Development of a Comprehensive Package for Stillbirth Reduction and Optimization of the implementation model and Phase 3: Scale-up of comprehensive package and monitoring of optimized strategy/model. Participants will include pregnant women, women who have recently delivered, family members, respectable community members, healthcare workers and staff, state and district health authorities. The effectiveness of intervention package and optimized implementation model in reducing stillbirth will be evaluated using a pre-post quasi-experimental design. The burden of stillbirth will be estimated through community survey, recording pregnancy outcomes for women who have delivered within the past one year. Various methods including semi-structured questionnaires, verbal autopsies, and in-depth qualitative interview guides, review of clinical case sheets will be used to assess the causes of stillbirth. Additionally, government health facilities will be assessed and strengthened over study period. This study will utilize implementation science theories, models, and frameworks (TMF), including the Consolidated Framework for Implementation Research (CFIR) to identify barriers and facilitators, and the evaluative TMF of RE-AIM (Reach Effectiveness Adoption Implementation and maintenance) to monitor the optimized model. The primary outcome is the development of a scalable, sustainable model of intervention package and delivery strategies to reduce stillbirths. The secondary outcome includes a robust estimation of burden, timing, and risk factors of stillbirths across all study sites. Certain sites will conduct an economic evaluation to assess the incremental cost of implementing comprehensive packages using the optimized implementation model. Discussion This innovative study addresses a critical public health gap in context of stillbirth reduction in India. Integrating proven interventions with real-world implementation challenges across diverse regions, this project aims to develop a comprehensive and replicable model. If successful, this model can significantly improve stillbirth prevention in low-resource settings. Trial registration ClinicalTrials.gov CTRI-2024/07/069796.